2021
DOI: 10.1186/s40001-021-00561-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between infection with Campylobacter species, poor oral health and environmental risk factors on esophageal cancer: a hospital-based case–control study in Thailand

Abstract: Background Previous studies have shown the association between Campylobacter species infection and that environmental factors, poor oral hygiene in particular, are linked to an increased risk of esophageal cancer (EC). However, no study has reported on these factors in Thailand. Thus, this study’s objective was to evaluate the impact of the relationship between Campylobacter infection and environmental factors on EC incidence in the population of Thailand. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(33 reference statements)
0
11
2
Order By: Relevance
“…The elevated abundance of Streptococcus in the gut microbiota is related to gastric cancer occurrence and liver metastasis (Yu et al, 2021). Although no evidence supports a direct relationship between Campylobacter and breast cancer, Campylobacter is related to esophageal cancer occurrence (Poosari et al, 2021). The commonly increased taxa Streptococcus, Campylobacter, and Moraxellaceae in BN and BM subjects could be risk factors for breast cancer occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated abundance of Streptococcus in the gut microbiota is related to gastric cancer occurrence and liver metastasis (Yu et al, 2021). Although no evidence supports a direct relationship between Campylobacter and breast cancer, Campylobacter is related to esophageal cancer occurrence (Poosari et al, 2021). The commonly increased taxa Streptococcus, Campylobacter, and Moraxellaceae in BN and BM subjects could be risk factors for breast cancer occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of published research has consistently demonstrated poor oral hygiene was associated with a higher risk of cancers, such as oral cancer (Deng et al, 2021), gastric cancer (Zhang et al, 2021), colorectal cancer (Wang et al, 2021). Based on the outcomes of two case-control studies, poor oral hygiene was an important risk factor for EC (Mmbaga et al, 2020;Poosari et al, 2021). And patients who received dental prophylaxis had a reduced risk of EC (Lee et al, 2014).…”
Section: Oral Hygienementioning
confidence: 99%
“…Other studies that suggested EC risk factors in Asian populations reported heterogeneous results from retrospective or casecontrol studies, and from cohort studies conducted decades ago, when environmental factors and lifestyles were very different. [27][28][29][30][31] There are obvious differences between risk factors and survival rates. The survival rate of SCC is lower than that of adenocarcinoma, so it is necessary to conduct a detailed comparative analysis of histological differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, tobacco and alcohol consumption are not strong risk factors in that belt. Other studies that suggested EC risk factors in Asian populations reported heterogeneous results from retrospective or case–control studies, and from cohort studies conducted decades ago, when environmental factors and lifestyles were very different 27–31 . There are obvious differences between risk factors and survival rates.…”
Section: Discussionmentioning
confidence: 99%